Functionalized solid electrodes for electrochemical biosensing of purine nucleobases and their analogues: a review - Sharma, Vimal Kumar; Jelen, Frantisek; Trnkova, Libuse (Sensors, 2015)
Interest in electrochemical analysis of purine nucleobases and few other important purine derivatives has been growing rapidly. Over the period of the past decade, the design of electrochemical biosensors has been focused on achieving high sensitivity and efficiency. The range of existing electrochemical methods with carbon electrode displays the highest rate in the development of biosensors. Moreover, modification of electrode surfaces based on nanomaterials is frequently used due to their extraordinary conductivity and surface to volume ratio. Different strategies for modifying electrode surfaces facilitate electron transport between the electrode surface and biomolecules, including DNA, oligonucleotides and their components. This review aims to summarize recent developments in the electrochemical analysis of purine derivatives, as well as discuss different applications.
Keywords: oxidace-redukce; elektrochemické techniky; Oxidation-Reduction; elektrody; Electrodes; puriny; Surface Properties; Purines; Electrochemical Techniques; povrchové vlastnosti; Biosensing Techniques; biosenzitivní techniky